Increased electroretinogram a‐wave amplitude after intravitreal bevacizumab injection for neovascular age‐related macular degeneration - Skaat, Alon; Solomon, Arie; Moroz, Iris; Hai, Orit Vidne; Rechtman, Ehud; Vishnevskia Dai, Vicktoria; Rotenstreich, Ygal (Acta ophthalmologica (Oxford, England), 2011)
. Purpose:  To assess the effect of bevacizumab (Avastin®), a vascular endothelial growth factor inhibitor, on retinal function by full‐field electroretinography (ERG) in patients with neovascular age‐related macular degeneration (AMD). Design:  A prospective, nonrandomized, controlled interventional clinical trial. Methods:  Twelve patients (aged 50−85) with neovascular AMD each received one unilateral intravitreal injection of bevacizumab 1.25 mg/0.05 ml as part of the standard management for choroidal neovascular AMD. Before and 1 month after injection, all patients underwent bilateral full‐field ERG scanning by a masked technician according to the ISCEV protocol, and their wave amplitudes were recorded. Untreated eyes served as controls. Scotopic responses were recorded at four incremental light intensities and photopic responses at two incremental light intensities. Changes in ERG‐amplitude responses were calculated. Repeated‐measures anova was used for data analysis. Results:  Mean pre‐ and postinjection differences in a‐wave amplitudes between the incremental light intensities in injected eyes were significantly higher than in controls (15.92 versus 1.33 μV for scotopic responses and 4.97 versus −1.06 μV for photopic responses; p = 0.057 and p = 0.01, respectively). Mean b‐wave amplitudes in injected eyes were significantly higher than in controls for photopic responses (p = 0.048), but for scotopic responses, the difference between treated and untreated eyes was not significant (p = 0.23). Conclusions:  Intravitreally injected bevacizumab improves both rod and cone functioning in patients with neovascular AMD, as demonstrated by the increase in the ERG a‐wave responses of these patients. Other measured ERG parameters yielded no significant photoreceptor toxicity.